Penerapan Hybrid Learning Berbasis Masalah Terhadap Critical Thinking Pembelajaran Fisika - Nurul Lailatul Muharromah; Sri Haryanto; Fatiatun (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Students' critical thinking ability plays an important role in the learning process, in order to improve students’ critical thinking, this study adopts a problem-based hybrid learning approach, in which learning combines two methods, online or offline, mplementing problem-based of learning study. The purpose of this degree is to understand the application of problem-based hybrid learning in improving students' critical thinking, and understand the extent to which students improve critical thinking in their physical studies. The real-world procedure used in this experiment uses the t-test statistic to analyze various tests of treatment effect, analyze reinforcement tests, and simultaneously test the magnitude of reinforcement increases. The results of this study show that: The application of problem-based blended learning in physics education is networked and face-to-face, starting from asking questions, collecting data, observing, discussing, and formulating conclusions from facts. Experimental grade growth test scores are in the high category, implying an increase in critical thinking in physics learning.